The Role of Dayah Ulama in Political Communication during the 2024 Aceh Elections - Arahman, Zulfikar; Alamsyah, Muhibuddin (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
Dayah ulama in Aceh play a central role in shaping social and political order through their strong moral legitimacy. In the 2024 Aceh regional election, their involvement reflects a shift from moral figures to strategic political actors. This study illustrates how dayah ulama’s political communication influences public participation and shapes local political dynamics. Using a qualitative approach, data were collected through in-depth interviews, observations, and thematic analysis. Findings show that dayah ulama utilize traditional preaching and modern strategies, such as social media, to expand political influence. [Added: Reference to integrative vs. polarizing impacts]. Their involvement goes beyond candidate support, constructing political narratives emphasizing pious leadership, sharia protection, and Islamic values in governance. While their communication reinforces shared cultural-religious identity, it can also sharpen social and political divisions depending on context. This contributes to broader discussions on faith-based political communication, showing parallels with global patterns where religious authority functions both as integrative and polarizing force in multicultural societies. Keywords: Political communication, dayah ulama, Aceh election, political participation, moral legitimacy ABSTRAKDayah ulama di Aceh memainkan peran sentral dalam membentuk tatanan sosial dan politik melalui legitimasi moral mereka. Dalam Pilkada Aceh 2024, keterlibatan mereka menyoroti pergeseran dari tokoh moral menjadi aktor politik strategis. Penelitian ini menggambarkan bagaimana komunikasi politik dayah ulama mempengaruhi partisipasi publik dan membentuk dinamika politik lokal. Dengan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam, observasi, dan analisis tematik. Temuan menunjukkan bahwa dayah ulama menggunakan metode khotbah tradisional dan strategi komunikasi modern seperti media sosial untuk memperluas pengaruh politik. [Added: Penekanan pada dampak integratif vs. eksklusif]. Keterlibatan mereka melampaui dukungan kandidat, membangun narasi politik tentang kepemimpinan saleh, perlindungan syariah, dan integrasi nilai Islam dalam pemerintahan lokal. Komunikasi mereka dapat memperkuat identitas budaya-agama bersama namun juga berpotensi mempertajam perpecahan sosial dan politik tergantung konteks. Kontribusi penelitian menghubungkan kasus Aceh dengan studi komunikasi politik global, menunjukkan fungsi ganda agama sebagai kekuatan pemersatu sekaligus sumber polarisasi.Kata Kunci: Komunikasi politik, dayah ulama, pilkada Aceh, partisipasi politik, legitimasi moral